2013
DOI: 10.1111/1365-2745.12176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plant invasions on local arthropod communities: a meta‐analysis

Abstract: Summary 1.Invasive plants can have a major impact on local plant and animal communities. However, effects of plant invasions on arthropod communities and the potential drivers have rarely been studied. 2. We present a meta-analysis of 56 studies on the impact of plant invasions on abundance and richness of local arthropod communities. Moreover, we study the role of five invader and habitat attributes to assess their influence on the direction and magnitude of effect on arthropod communities: the time since int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 73 publications
3
64
1
4
Order By: Relevance
“…Similar observations had been previously made by a large number of authors (e.g., Carpenter and Cappuccino 2005;Liu and Stiling 2006;Parker and Gilbert 2007;Proches et al 2008;Sugiura 2010;Harvey et al 2012;Litt et al 2014;van Hengstum et al 2014;Cronin et al 2015). However, in a significant amount of other studies, no difference in herbivory damage or abundance was found between native and exotic plants, especially when only congeneric native and exotic plant species were compared (e.g., Novotny et al 2003;Hawkes 2007;Sugiura et al 2008;Chun et al 2010;Dostál et al 2013), suggesting that the release from herbivory in the region of introduction is not a general pattern for exotic plants (Bezemer et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Similar observations had been previously made by a large number of authors (e.g., Carpenter and Cappuccino 2005;Liu and Stiling 2006;Parker and Gilbert 2007;Proches et al 2008;Sugiura 2010;Harvey et al 2012;Litt et al 2014;van Hengstum et al 2014;Cronin et al 2015). However, in a significant amount of other studies, no difference in herbivory damage or abundance was found between native and exotic plants, especially when only congeneric native and exotic plant species were compared (e.g., Novotny et al 2003;Hawkes 2007;Sugiura et al 2008;Chun et al 2010;Dostál et al 2013), suggesting that the release from herbivory in the region of introduction is not a general pattern for exotic plants (Bezemer et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…shown a negative impact of neophytes on insects (Tallamy 2004;Casagrande and Dacey 2007;Keeler and Chew 2008;Tallamy et al 2010;Fortuna et al 2013), which is confirmed by meta-analyses showing that non-invaded habitats, in comparison to habitats with a high proportion of alien species, had higher total abundance and taxonomic richness of arthropods (Bezemer et al 2014;van Hengstum et al 2014;Litt et al 2014). In situations where the optimal host is a rare species or there is high competition for food, the cost of feeding on the optimal host may be large enough for an insect that it favours the strategy of increasing the number of potential host plants by utilising a new species (Mayhew 1997).…”
mentioning
confidence: 68%
“…A disponibilidade de artrópodes na folhagem e na serapilheira pode diminuir com o aumento na densidade de PEIs, prejudicando populações de espécies das guildas insetívoras (Hengstum et al, 2014). No caso dos insetívoros do solo, alterações nas condições microclimáticas, como sombreamento e umidade relativa do ar, podem influenciar nos padrões de distribuição (Volpato et al, 2006).…”
Section: Discussionunclassified